Implementasi Pendidikan Islam Multikultural dan Moderat di Sekolah Dasar dalam Membentuk Nasionalisme - Oktoberi, Panca; Warsyah, Idi; Sirajuddin M, Sirajuddin M; Suhirman, Suhirman; Dali, Zulkarnain (JOEAI (Journal of Education and Instruction), 2021)
the surrounding environment as a plurality culture (contextual approach) and inculcating attitudes tolerance and being able to coexist with others. In conclusion, the implementation of multicultural and the surrounding environment as a plurality culture (contextual approach) and inculcating attitudes tolerance and being able to coexist with others. In conclusion, the implementation of multicultural and moderate islamic education in elementary schools in shaping nationalism is carried out in three steps developed by teachers in structured learning planning by formulating goals, setting important materials implementing learning processes, and conducting attitude assessment . Keyword: moderate, multicultural, nationalism, islamic education